Genetic and genomic signatures in ethanol withdrawal seizure-prone and seizure-resistant mice implicate genes involved in epilepsy and neuronal excitability - Zhou, Zhifeng; Metten, Pamela; Yuan, Qiaoping; Sun, Hui; Hodgkinson, Colin A.; Shen, Pei-Hong; Marietta, Cheryl; Crabbe, John C.; Goldman, David (Molecular psychiatry, 2022)
Alcohol withdrawal is a clinically important consequence and potential driver of Alcohol Use Disorder. However, susceptibility to withdrawal symptoms, ranging from craving and anxiety to seizures and delirium, varies greatly. Selectively bred Withdrawal Seizure-Prone (WSP) and Seizure-Resistant (WSR) mice are an animal model of differential susceptibility to withdrawal and phenotypes with which withdrawal severity correlates. To identify innate drivers of alcohol withdrawal severity, we performed a multi-omic study of the WSP and WSR lines and F2 mice derived from them, using genomic, genetic, and transcriptomic analyses. Genes implicated in seizures and epilepsy were over-represented among those that segregated between WSP and WSR mice and that displayed differential expression in F2 mice high and low in withdrawal. Quantitative trait locus (QTL) analysis of ethanol withdrawal convulsions identified several genome-wide significant loci and pointed to genes that modulate potassium channel function and neural excitability. Perturbations of expression of genes involved in synaptic transmission, including GABAergic and glutamatergic genes, were prominent in prefrontal cortex transcriptome. Expression QTL (eQTL) analysis fine mapped genes within the peak ethanol withdrawal QTL regions. Genetic association analysis in human subjects provided converging evidence for the involvement of those genes in severity of alcohol withdrawal and dependence. Our results reveal a polygenic network and neural signaling pathways contributing to ethanol withdrawal seizures and related phenotypes that overlap with genes modulating epilepsy and neuronal excitability.